Análisis jurídico de la contratación pública en las obras de construcción”, (menor cuantía, cotización, licitación, contratación integral por precio fijo) dentro del gobierno autónomo descentralizado de la provincia de Cotopaxi. - Huertas Vaca, Paúl Germánico (2013)
Nationally, the procurement of goods and services by government agencies that provide the necessary inputs which allow governments to provide public services and perform other tasks. Procurement systems, significantly impact on the efficient use of public funds and, more generally, in public trust in government and in its governance. Achieving a good balance between quality and price, public access to information on public contracts, and equitable opportunities for suppliers to compete in order to win public contracts, They are essential requirements of an efficient procurement system. The History of Public Procurement in Ecuador has been taking modernized steeps strides and always looking for ways to transparent all procurement processes in public institutions.